Variação quantitativa das populações de microorganismos de solo relacionada às variações microclimáticas - PANTOJA, Pedro Henrique Bonfim (2019)
This study is a proposal for a scientific contribution to the understanding of the interrelationship between population density of bacteria and fungus in the soil associated microclimate variability of seasonal rain forest, also considering an extreme event case study. The populations of microorganisms were studied for their distribution and density, using the Pour Plate "counting cards" Petri ", following the methodology proposed by De-Polli & Guerra (1999). This study was conducted in two experimental areas PPBio (area of dense natural forest) and ESECAFLOR (area of one acre covered to simulate drought) in Caxiuanã-PA, with continuous measurements of variables of temperature, humidity and precipitation, and evaluation of spatial patterns and temporal distribution of abundance and richness species, to establish a monitoring system micro soil fauna associated with climate variability in the national forest Caxiuanã. Microbiological analysis showed that the experimental areas are predominantly Typic and observed that fungal decrease with depth at both sites at any time of the year. In a related study the bacteria they present hypertext links shall go this pattern only in the natural site (PPBio) and excluding the site of water (ESECAFLOR) this behavior is irregular